UMPSA s TVET Adventure Basic Digital Design Training for SMK Kuala Krau students - Naqiah, Puaad (UMPSA, 2024)
KUALA KRAU, 11 October 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) provided Basic Digital Design training to students of Sekolah Menengah Kebangsaan Kuala Krau as part of the recent UMPSA@Kuala Krau TVET Adventure.